BRUXISM, PERLUKAH DIRAWAT? (TINJAUAN PUSTAKA) - Laura Susanti Himawan (Faculty of Dentistry, Universitas Indonesia, 2015)
Every dentist knows about bruxism. However, the etiology, the treatment, and the relationship between bruxism and temporomandibular disorders (TMD) are still unknown and controversional. Bruxism can happen to all ages, from children (15% of all children) to adults (96% of all adults), male and female. Given the data, what can a dentist do to help the patient with bruxism? The various clinical signs that can be found in these patients are excessive tooth wear, muscle and joint fatigue, headache, tooth sensitivity or mobility, fractures of teeth and restorations, as well as TMD symptoms. Currently no method can permanently eliminate bruxism, but there are several ways to help patients with symptoms caused by parafunctions. Two categories of bruxism are bruxism withous symptoms and bruxism with symptoms that lead to temporomandibular disorders. To make the patient aware of the destructive parafunctional activities, self-monitoring, biofeedback, medications, occlusal adjustment and fabricating a splint can reduce the unfavorable consequences of bruxism. Although they usually do not stop it. Periodical control is advisable.